2007 Computers in Cardiology 2007
DOI: 10.1109/cic.2007.4745494
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of low-intensity fluorescence signals in living cardiac cells using time-resolved laser spectroscopy

Abstract: In the aim to study calcium distribution and dynamics in single living left-ventricular rat cardiomyocytes, we have applied a new method for discrimination of the calcium probe fluorescence signal from the intrinsically fluorescing cell constituents. In a case study investigating calcium-sensitive dye Fluo-3, we have characterized the spectral and the lifetime fingerprints of the Fluo-3 fluorescence and of the cell flavin autofluorescence by spectrally-resolved confocal microscopy and/or by multiwavelength tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2009
2009
2010
2010

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Our previously obtained data in rat cardiomyocytes [6][7][8] clearly showed that metabolic state can be determined directly in living cardiac cells by monitoring their naturally occurring endogenous AF. Such AF, generated after excitation with UV or visible light is localized in mitochondria and is mainly resulting from mitochondrial oxidized flavins (FAD * ) and reduced NAD(P)H [9], principal endogenous indicators of cellular oxidative metabolism.…”
Section: Biophotonicsmentioning
confidence: 95%
See 1 more Smart Citation
“…Our previously obtained data in rat cardiomyocytes [6][7][8] clearly showed that metabolic state can be determined directly in living cardiac cells by monitoring their naturally occurring endogenous AF. Such AF, generated after excitation with UV or visible light is localized in mitochondria and is mainly resulting from mitochondrial oxidized flavins (FAD * ) and reduced NAD(P)H [9], principal endogenous indicators of cellular oxidative metabolism.…”
Section: Biophotonicsmentioning
confidence: 95%
“…We have now applied spectrally resolved TCSPC [8] method in cardiomyocytes from rat, as well as human hearts and studied spectral and lifetime properties of both the endogenous flavins [7,8], as well as the NAD(P)H [11,12], and thus gathered an additional information on functioning of enzymes responsible for generation of electrochemical gradient in the respiratory chain. Furthermore, we have used an original approach of multispectral imaging followed by spectral decomposition and linear unmixing [13,14] and developed analytical methods for the separation of individual components in spectrally-resolved confocal images [7] and time-resolved signals from both the cell AF [15] and fluorescence probes [16]. In addition to gathering a strong background in this spectroscopy technology, we have also successfully put in place the isolation of cardiac myocytes from human EMB biopsies, as demonstrated by our latest publication [12], where we also noted the rise in NAD(P)H fluorescence in cells from heart transplanted patients presenting mild rejection.…”
Section: Biophotonicsmentioning
confidence: 99%
“…Once the number of independent spectral components is known, the analysis can be followed by the creation of a reference spectra database. This is relatively easy for exogenous fluorescence probes, for which the reference spectra can be measured individually for each fluorophore in the sample [31], assuming that they do not change in the multi-fluorophore mixture. In the case of cellular AF, however, it is not easy and even not possible to biochemically isolate different native forms of enzymes and coenzymes, such as those of flavin adenine nucleotide (FAD) and/or nicotinamide adenine dinucleotide (phosphate) (NAD(P)H).…”
Section: Data Analysis Of Time-resolved Afmentioning
confidence: 99%
“…The data thus unmixed can be further processed by suitable methods of exponential analysis. The feasibility of quantitative lifetime unmixing to assess complex multi-spectral TCSPC data was demonstrated in isolated cardiac myocytes with calcium-sensitive probes [31], flavin fluorescence [29] and NAD(P)H (unpublished results), providing a highly-sensitive tool for optical fingerprinting of the metabolic state directly in living cells. A similar concept, applied to the analysis of cyan or green fluorophores recorded on frequency domain FLIM, was reported recently by G.-J.…”
Section: Data Analysis Of Time-resolved Afmentioning
confidence: 99%